PERAN AYAH (FATHERING) DALAM PENGASUHAN ANAK USIA DINI - Annisa Wahyuni; Syamsiah Depalina Siregar; Riris Wahyuningsih (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2021)
Abstract The father is a leader in the family who is an example for his family members, including children. so this study is to describe how the role of fathers in parenting in early childhood. With the involvement of the father it will help the growth and development of children. The researcher uses the Library Research approach . The findings of this study are that father involvement in parenting is a continuous active participation of fathers in child care which contains aspects of frequency, initiative, and personal empowerment in the physical, cognitive, and affective dimensions in all areas of child development, namely physical, emotional, social. , intellectual and moral. Thus the impact on the development of religion and its moral, cognitive and social emotional. on the development of gender roles, morals, achievement motivation, and on social development. In addition, the father as a male model in the family. So with the father's role in the family, he becomes a male role model in the family.